Oil-soluble contrast medium bathing attenuated endometrial inflammation and improved endometrial receptivity in women with recurrent implantation failure: a descriptive study - Qiuyan Huang; LinIing Mo; Junli Wang; Aiping Qin (BMC, 2024)
Abstract Background The oil-soluble contrast medium used in hysterosalpingography has been shown to have a fertility-enhancing effect, but the underlying mechanism is unclear, especially regarding the role of window of implantation (WOI). This study aimed to assess the endometrial immunological impact of the WOI before and after bathing with the oil-soluble contrast medium in women with recurrent implantation failure (RIF). Methods This descriptive study involved two medical centers between December 18, 2019, and December 30, 2020. We included infertile women who underwent three or more transfer cycles, cumulative transplantation of at least four high-quality cleavage-stage embryos or three high-quality blastocysts without clinical pregnancy, and high-quality frozen embryos that were still available for implantation. Patients received 5 ml of ethiodized poppyseed oil bathing, endometrial biopsy around bathing, and frozen-thawed embryo transfer (FET) within four menstrual cycles after bathing. Patients were excluded if failure to complete anyone. Data on the baseline characteristics and clinical data of the FET cycles were collected, and endometrial biopsy specimens were collected in the luteal phase before and after bathing and subjected to immunohistochemistry. The number of CD56 and CD138 positive cells and H-score of expression of ανβ-3 and HOXA10 in endometrium were collected. Results Thirty-four patients were initially enrolled in the study; ultimately, twelve patients with a median age of 32.5 years (range 27-40 years) completed the research. The median number of embryo transfer cycles was three (range 3-8). A total of 4 of 12 women (33.33%) were diagnosed with chronic endometritis before oil-soluble contrast bathing. After bathing, the median numbers of CD138-positive cells in endometrium decreased from 0.75 (range 0-13.5) to 0.65 (range 0-6), P = 0.035; additionally, the H-score of expression of ανβ-3 in endometrium increased from 148.50 ± 31.63 to 175.58 ± 31.83, P < 0.001. The thickness of the endometrium also significantly increased (8.90 ± 1.45 mm vs.10.11 ± 1.98 mm, P = 0.005). However, no consistent changes were found in the expression of CD56 and HOXA10 in the endometrium. Five patients experienced biochemical pregnancies (41.67%), four had clinical pregnancies (33.33%), and three achieved live births following oil-soluble contrast bathing (25%). Conclusions These results suggest that oil-soluble contrast medium bathing decreased CD138-positive cells and upregulated expression of ανβ-3 during WOI in patients with RIF. This histological impact of endometrium may result in enhanced fertility during FET cycles. Investigating the ability of intrauterine bathing with lower-dosage oil-soluble contrast to improve pregnancy in the RIF population is warranted.